Biometric relationships of the brown shrimp Penaeus subtilis (Pérez Farfante, 1967) in the Amazon River continental shelf - Aragão, José Augusto Negreiros; Petrere Júnior, Miguel; Cintra, Israel Hidenburgo Aniceto (Arquivos de Ciências do Mar, 2018)
In the present paper biometrics relationships between measures of body length and body weight of the brow shrimp Penaeus subtilis (Pérez Farfante, 1967) in the Amazon River continental shelf, were estimated. Samples obtained on board of the research vessel Alm. Paulo Moreira as well as samples obtained on the landings at the fishing companies in Belém, from 1995 to 1998 were used in the analysis. The equations were fitted utilizing the linear and non linear regression techniques based on the least squares and maximum likelihood methods respectively. Regressions were estimated for females and males taking in account the data over the entire period, grouped by quarter and year. It was found that females are larger than males and significant differences between the curves for the several regressions for males and females were verified. Expressive differences between the parameters estimated here and the parameters presented by other authors in previous studies were also found. The values of the condition factor were always higher for larger individuals, suggesting the presence of mature individuals throughout the year, but to a lesser extend in the first trimester.